Kocuria Bacterial Isolates from Radioactive Springs of Jáchymov spa (Joachimsthal) as Sources of Polyunsaturated Fatty Acids - Řezanka, Tomáš; Gharwalová, Lucia; Nováková, Gabriela; Kolouchová, Irena; Uhlík, Ondřej; Sigler, Karel (Lipids, 2019)
Four bacterial isolates, which produced polyunsaturated fatty acids (PUFA), were isolated from water samples of radioactive springs collected from Jáchymov spa. Jáchymov (Sankt Joachimsthal) is a city in northwestern Bohemia, where Marie and Pierre Curie isolated radium in 1898 from the mineral uraninite. To date, four springs (Agricola, Behounek, C1, and Curie) have been used for spa purposes, that is for the treatment of nervous and rheumatic disorders by constantly produced radioactive gas radon (222 Rn) dissolved in the water. The radioactivity reaches 24 kBq/L. Using 16S rRNA gene sequence analysis, all four isolates were identified as members of the genus Kocuria, with two isolates designated 208 and 401 affiliated with Kocuria kristinae, while isolates 101 and 301 most likely with K. rhizophila. The content of fatty acids in polar lipids was determined by gas chromatography-mass spectrometry (GC-MS) and two PUFA, that is arachidonic and eicosapentaenoic, were identified. The position of double bonds was confirmed by GC-MS of 3-pyridylcarbinol (formerly picolinyl) esters. We assume that all four isolates of Kocuria produce PUFA to increase the stability of cell membranes, which may be impaired by the reaction of the reactive oxygen species. These can arise, for example, because of α radiation during 222 Rn decay.
Keywords: zastoupení bazí; Radioactive springs; RNA, Ribosomal, 16S; Fatty Acids, Unsaturated; Natural Springs; Micrococcaceae; Water Microbiology; mikrobiologie vody; Jáchymov spa; Kocuria sp.; nenasycené mastné kyseliny; RNA ribozomální 16S; Arachidonic and eicosapentaenoic acids; přírodní prameny; Base Composition; Polyunsaturated fatty acids